Association between early intubation and mortality in patients at high risk for noninvasive ventilation failure: a propensity-matched cohort study - Tao Huang; Lijuan Chen; Xiaoyi Liu; Ke Wang; Weiwei Shu; Lei Jiang; Linfu Bai; Wenhui Hu; Mengyi Ma; Jun Duan (Therapeutic Advances in Respiratory Disease)
Background: Noninvasive ventilation (NIV) is frequently employed for acute hypoxemic respiratory failure, yet optimal intubation timing for high-risk NIV failure patients remains uncertain. Objectives: To investigate mortality outcomes associated with early versus late intubation in high-risk NIV failure patients. Design: Secondary analysis of a multicenter observational cohort study. Methods: Patients with high NIV failure risk (updated HACOR score ⩾11 after 1–2 h of NIV) were enrolled. We defined that intubation was needed in these high-risk patients. Intubation occurring within 12 h of NIV initiation was classified as early intubation, while intubation after 12 h was designated as late intubation. Primary outcomes were intensive care unit (ICU) and hospital mortality. In sensitivity analyses, patients who achieved NIV success were categorized into the late-intubation group. Due to baseline imbalances, propensity score matching was performed with covariate adjustment. Results: Among the study population, 171 patients underwent early intubation and 222 underwent late intubation. Despite greater baseline severity in the early intubation group, ICU mortality (36% vs 58%, p  < 0.001) and hospital mortality (38% vs 58%, p  < 0.001) were significantly lower compared to the late-intubation group. In sensitivity analyses, 190 patients with NIV success were included in the late-intubation group, further accentuating the severity disparity between groups. After propensity matching (220 patients: 110 per group), most of the baseline characteristics were comparable. The early intubation group had a 100% intubation rate versus 71% in the late-intubation group, with the latter exhibiting higher mortality (ICU: 46% vs 32%, p  = 0.052; hospital: 50% vs 34%, p  = 0.020). Conclusion: In patients at high risk for NIV failure, early intubation is associated with reduced mortality.